2021
DOI: 10.5334/ijic.5501
|View full text |Cite
|
Sign up to set email alerts
|

A Community Resource Navigator Model: Utilizing Student Volunteers to Integrate Health and Social Care in a Community Health Center Setting

Abstract: Introduction: While unmet social needs are major drivers of health outcomes, most health systems are not fully integrated with the social care sector to address them. In this case study, we describe the development and implementation of a model utilizing student volunteer community resource navigators to help patients connect with community-based organizations (CBOs). We then detail initial implementation outcomes and practical considerations for future work. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 33 publications
1
57
0
Order By: Relevance
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…Of the 24 studies that included clinician-administered screening, 1 used medical providers to screen patients, 37 7 used medical residents, [35][36][37][38][39]89,90 1 used a combination of clinical and social care staff (eg, nurse, social worker, medical assistant), 40 and 15 used paid social care staff (eg, case managers, community health workers, navigators) or volunteers. [26][27][28]31,33,[49][50][51]57,60,63,74,78,85,88 In the 8 models using medical providers or residents, they either (1) assisted patients directly through community resource referrals, 38,39 (2) provided community resource referrals with an option to escalate to a social worker or an on-site medical legal partnership, 36,37,47,90 or (3) directly referred patients to social work or the onsite medical legal partnership without providing community resource information themselves. 35,89 In the 15 models that used social care staff or non-physician clinical staff to administer screenings, the same worker who conducted the screening was the same worker to provide initial assistance to patients, 31,36,40,41,44,55,56,58,61,…”
Section: Screening and Responding To Unmet Needsmentioning
confidence: 99%
See 3 more Smart Citations